Primary Cerebellopontine Angle Melanocytoma: Review - Phang, Isaac (Georg Thieme Verlag KG, 2012)
Introduction Primary cerebellopontine angle melanocytomas (PCPAMs) are very rare. Their natural history and prognosis are not fully understood. We reviewed the literature and add a new case to analyze PCPAM's presentation, radiological features, and outcome of treatment. Methods We performed a literature review using Medline, Embase, PubMed, and Cochrane databases. We searched for melanocytoma, melanoma, and pigmented tumors in the posterior cranial fossa and CPA to identify PCPAM. We have also searched our institution's neuro-oncology database. Results We identified 23 PCPAM from the literature and one case of our own. The mean age at presentation was 44.4 years with slight male preponderance. PCPAM presented with cerebellopontine angle (CPA) syndrome with or without hydrocephalus. Preoperative diagnosis was difficult; they appeared hyperintense on T1 and isointense on T2 magnetic resonance imaging (MRI) and enhanced with gadolinium. However, the final diagnosis was only made by immunohistochemical examination. Total surgical resection of PCPAM was associated with prolonged survival while subtotal excision was associated with frequent recurrence. Conclusion PCPAM are very rare and should be considered in the differential diagnosis of all CPA lesions that appear hyperintense on T1 and isointense on T2 MRI images. Patients with PCPAM should undergo total surgical resection to avoid fatal recurrences.